Sobre o tempo : perspectivas históricas no pensamento de Friedrich Nietzche - Juraski, Vanderlei Cristiano (2013)
This study aims to analyze the relationship between man and time. Put another way, to what extent the naturalization of time can overwhelm the individual or allow the creative forces develop up about their existence? From the works of Friedrich Nietzsche (1844-1900), especially the untimely II: on the usefulness and disadvantages of history for life (1874) and Thus Spoke Zarathustra: a book for everyone and nobody (1885), glimpsed the possibility of treating history, produced in the eighteenth and nineteenth century, as a representation of social needs, and not only as the "naturalization" of the time. The methodology was initially to analyze two distinct ideas: linear and cyclical time, as well as the implications (social)behaviors that result from incorporating any of the above concepts. Both situations allow a reflection on how the individual should behave before the birth, aging and death. In the first case, for example, in the case of a non-historical reality, the position of man to life proves different from that observed in a second moment, that there can only be accepted, considering the temporal experiences as measurable historically. History, in this sense, becomes a target of political disputes, since it expresses the need for rationalization of the universe, and the identification of the individual with the collective past. For historian therefore is subject to all the measurement and thus lineage. The trespass interest in the past in search of continuities and otherwise, prevent disruptions, weaving the narrative in a rational and scientific, appears to be the first step to formalize and evict man from his own experiences and time, giving the historian, the monopoly of the narration. The eternal return, in turn, was the Nietzschean strategy for reconnecting the historiography of life. The perception that the living may happen again in the present, as well as a perspective on the fait accompli, it is shown how the valuation of this; shares worth repeating itself countless times in the future, returning, in a sense, sense when making historiographical.